1997
DOI: 10.1128/aac.41.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of voriconazole (UK-109,496) and itraconazole in prevention and treatment of Aspergillus fumigatus endocarditis in guinea pigs

Abstract: Left-sided Aspergillus fumigatus endocarditis was established in the guinea pig heart by catheterization and inoculation with conidia via a tributary of the femoral vein. This animal model was used to compare the efficacy of the triazole antifungal agents voriconazole (UK-109,496) and itraconazole. In the prophylaxis experiments, voriconazole at a dosage of 10 mg/kg of body weight given intraperitoneally twice daily prevented A. fumigatus endocarditis in all but 1 animal (11 of 12 animals were cured). Itracona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(37 citation statements)
references
References 11 publications
0
37
0
Order By: Relevance
“…A recent, randomized, prospective study of patients with documented cases of invasive aspergillosis showed that patients treated with voriconazole had improved survival rates 12 weeks after initiation of therapy, compared with patients treated with amphotericin B (70.8% vs. 57.9%) [4]. Experimental models have also demonstrated the potential superior efficacy of treatment with voriconazole [5,6]. We hypothesize that voriconazole may have improved tissue penetration, leading to the improvements in clinical efficacy noted.…”
mentioning
confidence: 82%
“…A recent, randomized, prospective study of patients with documented cases of invasive aspergillosis showed that patients treated with voriconazole had improved survival rates 12 weeks after initiation of therapy, compared with patients treated with amphotericin B (70.8% vs. 57.9%) [4]. Experimental models have also demonstrated the potential superior efficacy of treatment with voriconazole [5,6]. We hypothesize that voriconazole may have improved tissue penetration, leading to the improvements in clinical efficacy noted.…”
mentioning
confidence: 82%
“…This was attributed to rapid rst pass metabolism and rapid clearance of the drug with repeated dosing [11]. As a result, other animals needed to be used to assess in ×i×o ef cacy, and the guinea pig has assumed a critical role in the preclinical testing of this compound [3,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…These promising in-vitro data seem to corroborate the encouraging in-vivo results from early clinical trials and several experimental models. 5,6 We also observe that the guidelines suggested by the NCCLS subcommittee on antifungal susceptibility testing appear to be suitable for testing the filamentous fungi Aspergillus spp. and that RPMI 1640 medium sustains the adequate growth of all isolated Aspergillus strains at 48-h incubation.…”
Section: Resultsmentioning
confidence: 99%
“…4 Voriconazole has also been found to be effective in experimental models of pulmonary aspergillosis and in the prevention and treatment of Aspergillus endocarditis in guinea pigs. 5,6 In this study, we determined the in-vitro activity of voriconazole, compared with that of other antifungal agents, against clinical isolates of Aspergillus spp. Invitro susceptibility testing was performed using the broth microdilution version of the National Committee for Clinical Laboratory Standards (NCCLS) reference method described in the M27-A document, and a colorimetric method using alamar blue.…”
Section: Introductionmentioning
confidence: 99%